Churchill by Himself : In His Own Words. - Churchill, Winston S. (RosettaBooks, 2013)
Quotations by the great statesman who helped lead Britain through two world wars: "Magisterial ... Should be in the library of every Churchill aficionado" (American Spectator). We shall fight on the beaches, we shall fight on the landing grounds, we shall fight in the fields and in the streets, we shall fight in the hills; we shall never surrender! Millions have been moved by these words'and by the hundreds of speeches given by Winston Churchill to rally the British public, spur its government to armament against Hitler, and defend the causes for which he believed. Churchill by Himself is the first collection of quotations from a leader who had as much talent for wit as he had for inspiration and exhortation. Edited by renowned Churchill scholar Richard Langsworth, this volume is the definitive collection of important quotes from one of the twentieth century's most persuasive and brilliant orators, whose writings earned him a Nobel Prize in Literature in 1953.